1984
DOI: 10.1111/j.1600-0447.1984.tb02502.x
|View full text |Cite
|
Sign up to set email alerts
|

Life events occurring before and after onset of depression in a Kenyan setting ‐ any significance?

Abstract: In a controlled study of life events in depressed patients in Kenya it was found that the rate of life events was higher in the depressed group in the 27 weeks preceding the onset of depression but with a sharp increase in the last 6-9 weeks before onset. It was also found that the depressed patients continued to experience independent life events after the onset of the depression. It is hypothesized that the continued occurrence of life events after the onset of depression is an incentive to seek help and, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 12 publications
4
6
0
Order By: Relevance
“…Hence the mean life event score for our subjects (2.2 B 1.7) is much higher than the mean life event scores of the schizophrenics (0.83 B 0.92) in the other Nigerian study. This is in support of previous African studies that have indicated the preponderance of life events among depressed patients [27,28]. The scientific literature seems to be silent on the relationship between age and life event scores.…”
Section: Life Eventssupporting
confidence: 79%
See 2 more Smart Citations
“…Hence the mean life event score for our subjects (2.2 B 1.7) is much higher than the mean life event scores of the schizophrenics (0.83 B 0.92) in the other Nigerian study. This is in support of previous African studies that have indicated the preponderance of life events among depressed patients [27,28]. The scientific literature seems to be silent on the relationship between age and life event scores.…”
Section: Life Eventssupporting
confidence: 79%
“…Following Gureje's [26] example, items 3,12,16,19,20,23,24,27, and 31 were classified as desirable life events, while the other items were regarded as undesirable (table 3). This instrument has been found to be acceptable to Nigerian subjects [26].…”
Section: Methods and Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, depressed patients experienced more life events than general population controls in a period of six months before the interview date, a common finding in past literature (Patel et al, 1997;Rafanelli et al, 2005). Life events significantly had more negative impact ratings among the depressed which is also consistent with earlier findings from the region (Birabwa, 2005;Ndetei et al, 1984). Independent life events were associated with an increased risk of current MDEs in patients compared to general population controls (Christensen et al, 2003;Paykel, 2003).…”
Section: Discussionsupporting
confidence: 81%
“…However the social environment may provide different mediating factors related to extended family structure and religious belief. Adult studies have found more life events before the onset of depression in Kenya (Ndetei & Vadher, 1984) but not before schizophrenia (Gureje & Adewunmi, 1988) in Nigeria, reminding us that western findings may not obtain in radically different cultures.…”
Section: Introductionmentioning
confidence: 99%